A new depside and a new secoiridoid from the aerial parts of Gentiana olivieri from flora of Turkey. Issue 9 (3rd May 2022) - Kırmızıbekmez, Hasan; Tatar, Deniz; Erdoğan, Murat; Kúsz, Norbert; Hohmann, Judit
Abstract: A new depside, olivieridepside (1 ), and a new secoiridoid, olivierigenin (2 ) were isolated from the aerial parts of Gentiana olivieri Griseb. along with four known compounds, gentiopicroside (3 ), olivierosides A (4 ) and B (5 ) and isoorientin (6 ). The structures of the isolates were determined by extensive 1 D and 2 D NMR spectroscopy and HR-MS analysis. This is the first report on the occurrence of a depside structure in the genus Gentiana . Moreover, a rare type of non-glycosidic secoiridoid (2 ) lacking an oxygenated group at C-1 is also being reported for the first time from this genus. The chemotaxonomic importance of the isolates was discussed in detail. Graphical Abstract: